ASSESSMENT OF SUITABLE LANDFILL SITE USING GEOSPATIAL TECHNIQUES: A CASE STUDY OF RAIPUR URBAN REGION, CHHATTISGARH, INDIA - Multaniya, Amit P; Verma, Sanju; Beg, M. K (International Journal of Research -GRANTHAALAYAH, 2021)
Currently, the solid waste management work of Raipur is being done in a completely traditional way, which is very expensive and time consuming. The site selection method using Geospatial techniques can function as a decision support tool for enhanced efficient and effective management of municipal solid waste. This Study’s aim was to develop landfill siting by crossing major barriers such as political, economic and environmental pressures for the execution of a suitable site criteria by employing combination of geospatial technique and Weighted Linear Combination (WLC) of Multi-Criteria Decision Analysis (MCDA) in Raipur urban area. The preliminary step of the methodology was geospatial operation and Study that disqualified all areas unsuitable for landfill siting. The insularity of suitable criteria for landfill site was generated based on published information on solid waste management, existing laws and regulatory necessities, as well as the existing local conditions. The different suitability criteria considered are soil, land use land cover, digital elevation model (DEM), surface waters, transport network, lithology and geological structures. Criteria were mapped using the geospatial technique; each criterion was identified and weighted by score for overlay to create suitability maps using GIS. The final results showed that there are more locations for landfills for Raipur urban area. In the present Study there are sporadic areas identified as suitable sites for landfill location. In the site suitability analysis 74.79% area found not suitable for landfill siting, 20.93% least suitable and 3.25% moderate suitable. Out of the remaining area, 1.03% area is found most suitable.